PTH-041 A High Quality Transient Elastography Service Can Successfully Be Delivered By Healthcare Assistants. (9th June 2014) - Patanwala, I; Fielding, S; Akerboom, K; Barr, J; Cross, T; Lombard, M; Richardon, P; Caldwell, H
Abstract : Introduction: Surrogate assessment of liver fibrosis by means of liver stiffness measurement (LSM) by transient elastography is well validated in different cohorts of patients with liver disease and is now a part of routine hepatological practice. There is an increasing demand for LSM in view of its role in managing patients with dermatological or haematological conditions who are on potentially fibrogenic therapy. Referrals for LSM in our unit have increased significantly over the last 12 months. Traditionally, specialist liver nurses have been trained to deliver this service. However, LSM by transient elastography is an easily transferable skill and therefore in a bid to reduce waiting times and make the service as cost effective as possible, we trained healthcare assistants (HCA) to perform LSMs. The aim of this review was to assess the impact of this change on the quality of LSM as measured by success rate and failed scans. Methods: A transient elastography service delivered by trained specialist liver nurses was set up in our hospital in May 2010. In July 2013, 3 HCAs were trained to carry out LSM using a Fibroscan®. The HCAs were initially trained by the manufacturers of the Fibroscan ® unit (Echosens Europe) and then underwent a period of formally observed training with formative and summative work place based assessments. After competency was ascertained, the HCAs were independently allowed to carry out LSMs. A retrospective review of all LSM reports from January 2013 to December 2013 was carried out and success rate of the tests were recorded. Any repeat requests due to failure were also recorded. Results: A total of 876 LSM were performed during the review period. 542 LSMs were performed by trained nurses and 334 by trained HCAs. There was no statistically significant difference in the mean success rate between nurses (96% SD 11.9%) and HCAs (96.4% SD 11.7%) (p = 0.699, 2 sample T Test) nor the proportion of LSMs with 100% success rates between the two groups (78.4 vs. 82.3% p = 0.151, Fisher's exact test). Furthermore, there were no statistical differences in any central measure of the observed interquartile ranges of the reported LSM between the 2 groups (p = 0.255). No LSM was repeated when performed by HCA for reasons of failure. Conclusion: LSM using a Fibroscan ® can be accurately performed by appropriately trained HCAs. The introduction of this change in practice has allowed a reduction in waiting time for LSM to within 2 weeks without affecting the quality of the service and allowed a more efficient use of resources. A high quality transient elastography service can be delivered by HCAs. Disclosure of Interest: None Declared.